IMPACT OF RECEIVING RASTRA SOCIAL ASSISTANCE AND CASH SOCIAL ASSISTANCE IN THE SUNGAI RAYA - Dwita, Febrisi; Agustine, Leony; Andri, Andri; Supardi, Supardi; Manurung, Rinto (Jurnal Sosial Humaniora, 2023)
The existence of the covid 19 pandemic that hit in Indonesia, requires the government to improve the welfare of the people affected by the Covid-19 pandemic through the Ministry of Social Affairs in designing strategies or programs such as social assistance. The purpose of this study was to determine the acceptance of social assistance in the form of rastra assistance and cash social assistance provided to Sungai Raya Dalam villagers, as well as further information regarding the impact of this assistance on residents affected by Covid 19. A qualitative descriptive method was used as the research method, using data collection techniques namely interviews, observation, and documentation. The data analysis technique used in this study is narrative analysis, where this technique focuses on the social context where communication can occur between respondents and researchers. As for the determination of the sample used as respondents in this study using snowball sampling, so that the respondents were categorized as informants, namely the management in the village of Sungai Raya Dalam, both village heads, secretaries, and local village officials as many as 10 informants. The results of the study show that the management of Covid-19 assistance in Sungai Raya Dalam Village is not optimal. The benefits of this assistance need to be socialized so that people are aware of the importance of reporting personal information so that there is no duplication of information in Sungai Raya Dalam village.